(3QTaGJ Cgd GdceGd hfSeGJ bQH Cgd GdhUGds - (3YHO GdQMef Hf YHO Gddg Hf CMeO HGabjg Ydhj,J (B1162 (3g` s ((3Ydi Hf YHO Gddg Hf GdMSjf Hf TgGH GdOjf s)
(3ChdgG (B:s
(3HGdeSLO GdMQGe efG Ydjce Cced GdSdGe s
(3BNQgG (B:s
(3hBdg hUMHg hef gOi HgOjg Edi ebGe YGdi EfJgJ GdQTaGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI efbhdI Yf fSNI HNW eMeO Hf YHO Gddg HGShOGf Yf fSNI HNW hGdOg YHO Gddg Yf fSNI HNW WGgQ Hf GdMSjf Hf WGgQ s
(3HChdgG Jedjc jYhO Edi SfI (B1274(3g` s
(3cJHJ GdYfGhjjf HGdMeQI s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs